The Impact of Applying Professionalism on Employees’ Performance in Governmental Organizations: A Field Study on Administrative Employees at King Abdulaziz Hospital -Jeddah - Al-Sherif, Khlood (The Arab Journal of Administration, 2023)
This study aimed to reveal the impact of (personal, career, organization) professionalism on the performance of administrative employees at King Abdulaziz Hospital in Jeddah. It was based on the descriptive analytical approach; the questionnaire was used as a data collection tool. It was applied to a sample of (223) out of (532) employees working at the Hospital. The sample was randomly selected and the data was statistically processed by using SPSS. The study found several results، the most important is: There is a high level of applying personal, career and organizational professionalism on Employees’ Performance at King Abdulaziz University Hospital. It also showed a relationship between the variables of the study -the impact of personal professionalism and employees’ performance- due to the variable of age. However, there was no relationship between the variables of the study – the impact of (career and organization) professionalism and employees’ performance - due to the variables of (age, qualifications, years of experience and the number of training courses). Several recommendations were submitted، including: Developing personal professionalism traits from a young age by inculcating values, identifying weakness and strength sides of the employee to enhance them through creating a suitable model for performance appraisal, enhancing job skills and professional skills through providing specialized courses, developing a fair and varied system of incentives corresponding with the needs of the working individual in order to encourage employees to perform professionally, and providing internal or external scholarships for employees to motivate self-development and improving employees educational capabilities (qualifications) and experiences.